2003
DOI: 10.1073/pnas.1131995100
|View full text |Cite
|
Sign up to set email alerts
|

Two Arabidopsis circadian oscillators can be distinguished by differential temperature sensitivity

Abstract: Circadian rhythms are widespread in nature and reflect the activity of an endogenous biological clock. In metazoans, the circadian system includes a central circadian clock in the brain as well as distinct clocks in peripheral tissues such as the retina or liver. Similarly, plants have distinct clocks in different cell layers and tissues. Here, we show that two different circadian clocks, distinguishable by their sensitivity to environmental temperature signals, regulate the transcription of genes that are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
138
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 52 publications
13
138
1
Order By: Relevance
“…The stability of a number of transcripts has been shown to be under circadian control (41), and the stability of others, including CCA1 and LHY, is light regulated (11). The stabilization of CAT3 mRNA in extended dark obscures an underlying rhythm in CAT3 transcription (24,42). Perhaps elevated temperature during the subjective night destabilizes PRMT5 mRNA, preventing the continued accumulation of PRMT5 mRNA at night in the absence of thermocycles.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of a number of transcripts has been shown to be under circadian control (41), and the stability of others, including CCA1 and LHY, is light regulated (11). The stabilization of CAT3 mRNA in extended dark obscures an underlying rhythm in CAT3 transcription (24,42). Perhaps elevated temperature during the subjective night destabilizes PRMT5 mRNA, preventing the continued accumulation of PRMT5 mRNA at night in the absence of thermocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Most probably reflecting this latitudinal trend, many tree species show marked clines in the critical short-day length that induces bud set at both the phenotypic and allelic level, resulting in bud set at earlier calendar dates and longer days in more northern populations (Bohlenius et al 2006;Hall et al 2007;Luquez et al 2008). Within species or genera, chilling cues may become subordinate to photoperiod cues in the timing of bud burst closer to the tropics and/or the temperatures required to fulfil chilling requirements may rise (Borchert et al 2005;Wilkie et al 2008;Colasanti & Coneva 2009 et al 2002), circadian clock period (Michael et al 2003) and day length sensitivity (Balasubramanian et al 2006a; but see Samis et al 2008) have all been identified. Overall developmental rates or response to endogenous cues may also shift with climate.…”
Section: Seasonal Cues Regulating Plant Phenologymentioning
confidence: 99%
“…Because both PRR7 and PRR9 also participate in clock responses to light (17), temperature entrainment and light entrainment appear to share components. However, the relative contributions of light and temperature to entrainment of the Arabidopsis clock are not well understood, except for the possibility of two oscillators capable of distinguishing light and temperature cues (18).…”
mentioning
confidence: 99%